A NEW IDENTIFYING POTENTIALLY UNUSUSAL FILE TRANSFERS OR DUPLICATION’S IN CLOUD ENVIRONMENTS - Dr.BASKAR NANJAPPAN, N.CHANDRIKA, M.SRIDEVI, P.THANMAY SREE, P.DIVYA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
There has been a prolific rise in the popularity of cloud storage in recent years. While cloud storage offers many advantages such as flexibility and convenience, users are typically unable to tell or control the actual locations of their data. This limitation may affect users’ confidence and trust in the storage provider, or even render cloud unsuitable for storing data with strict location requirements. To address this issue,We equip each cloud node with a socket monitor that is capable of monitoring the real-time communication among cloud nodes. Based on the real-time data transfer information captured by the socket monitors, our system calculates the probability of a given transfer to be illegal. We have implemented our proposed framework and carried out an extensive experimental evaluation in a large-scale real cloud environment to demonstrate the effectiveness and efficiency of our proposed system.